Systematic review and meta‐analysis of intravenous iron therapy for adults with non‐anaemic iron deficiency: An abridged Cochrane review. Issue 6 (2nd November 2022) - Dugan, Cory; Cabolis, Katerina; Miles, Lachlan F.; Richards, Toby
Abstract: Iron is an essential nutrient for oxygen supply and aerobic metabolism. Iron deficiency impacts cellular respiration and mitochondrial energy metabolism, which can lead to reduced skeletal muscle function and muscle mass, causing sarcopenia. Intravenous iron offers the ability to rapidly correct iron deficiency, but the functional impact on patient mental and physical health is unclear. We assessed the effects of intravenous iron therapy on physical function and quality of life in the treatment of adults with non‐anaemic iron deficiency. An update and reanalysis of a previously published Cochrane systematic review was performed to assess randomized controlled trials that compared any intravenous iron preparation with placebo in adults. The primary functional outcome measure was physical performance as defined by the trial authors. Secondary outcome measures included fatigue and quality‐of‐life scores, and adverse effects at the end of follow‐up. Biochemical efficacy was assessed by change in serum ferritin and haemoglobin concentration levels. Twenty‐one randomized controlled trials, comprising 3514 participants, were included. Intravenous iron compared with placebo resulted in significantly increased physical function measured by mean peak oxygen consumption (mean difference [MD] 1.77 mL/kg/min, 95% confidence interval [CI] 0.57 to 2.97). An overall improvement in fatigue was seen (standardized MD 0.30, 95% CI −0.52 to −0.09) but no overall difference in quality of life (MD 0.15, 95% CI −0.01 to 0.31). Biochemically, intravenous iron resulted in improved serum ferritin (MD 245.52 μg/L, 95% CI 152.1 to 338.9) and haemoglobin levels (MD 4.65 g/L, 95% CI 2.53 to 6.78). There was a higher risk of developing mild adverse events in the intravenous iron group compared with the placebo group (risk ratio 1.77, 95% CI 1.10 to 2.83); however, no differences were seen in serious adverse events (risk difference 0, 95% CI −0.01 to 0.01). The quality of evidence was rated 'low' and 'very low' for all outcome variables, except for fatigue, mainly due to most studies being judged as having a high risk of bias. In non‐anaemic iron‐deficient adults, the use of intravenous iron compared with placebo improved physical function and reduced fatigue scores. However, we remain uncertain about the efficacy in this population due to low‐quality evidence, and there is a need for further studies to address potential impact on overall quality of life.